Clinicopathological significance of CD28 overexpression in adult T‐cell leukemia/lymphoma. Issue 1 (29th November 2021) - Sakamoto, Yuma; Ishida, Takashi; Masaki, Ayako; Takeshita, Morishige; Iwasaki, Hiromi; Yonekura, Kentaro; Tashiro, Yukie; Ito, Asahi; Kusumoto, Shigeru; Iida, Shinsuke; Utsunomiya, Atae; Ueda, Ryuzo; et al.
Abstract: CD28, one of the costimulatory molecules, has a pivotal role in T‐cell activation, and its expression is strictly regulated in normal T cells. Gain‐of‐function genetic alterations involving CD28 have been frequently observed in adult T‐cell leukemia/lymphoma (ATLL). These abnormalities, such as CD28 fusions and copy number variations, may not only confer continuous, prolonged, and enhanced CD28 signaling to downstream pathways but also induce overexpression of the CD28 protein. In this study, 120 ATLL cases were examined by immunohistochemistry for CD28 and its ligands CD80 and CD86, and their expression on tumor cells was semiquantitatively evaluated. CD28 was overexpressed in 55 (46%) cases, and CD80 or CD86 (CD80/CD86) was infrequently overexpressed in 12 (11%). Compared with non‐overexpressers, CD28 overexpressers showed a higher frequency of CD28 genetic alterations and had an increased number of CD80/CD86‐positive non‐neoplastic cells infiltrating tumor microenvironment. In the entire ATLL patient cohort, CD28 overexpressers showed a significantly poorer overall survival (OS) compared with non‐overexpressers ( P  = .001). The same was true for a subgroup who were treated with multidrug regimens with or without mogamulizumab. CD28 overexpression had no prognostic impact in the group who received allogeneic hematopoietic stem cell transplantation. In the multivariate analysis for OS, CD28 overexpression was selected as an independent risk factor. These results suggest ATLL patients with CD28 overexpression have more aggressive clinical course and are more refractory to treatment with multidrug chemotherapy. CD28 overexpression appears to be a novel unfavorable prognostic marker in ATLL patients, and further prospective studies are warranted to establish its prognostic significance. Abstract : The aim of the present study was to determine the clinicopathological significance of CD28 overexpression in adult T‐cell leukemia/lymphoma (ATLL). CD28 overexpression is associated with unfavorable prognosis of ATLL patients who were treated with multidrug regimens including mogamulizumab; thus, CD28 overexpression appears to be a novel unfavorable prognostic marker in ATLL.